Dampak Kejadian Kadaluawarsa Terhadap Gugatan yang Dapat Memberikan Kepastian Menuntut Menjadi Gugur dalam Hukum Indonesia - Urbanisasi Urbanisasi; Rosnawati Sasmita (Journal of Innovative and Creativity, 2025)
The purpose of this study is to provide an overview of the impact of statutes of limitations or the influence of the past on cases in the legal system. The provisions of the statute of limitations can impact the certainty of a person's right to file a lawsuit or demand fulfillment of obligations in a court of law. The rights of victims and perpetrators may be affected by the statute of limitations. Most significantly, it provides legal certainty for defendants that after a certain time limit, they can no longer be held responsible for a past agreement or legal act. Statutes provide a time limit for filing a claim, which can limit the victim's right to seek justice after a certain period, while also protecting perpetrators from claims that are beyond time. The law seeks to ensure that victims have access to justice within a reasonable time period, while perpetrators are protected from claims that are too long.